Film jako ilustracja ról społecznych. Obraz matki w wybranych filmach Alfreda Hitchcocka - Juszczak , Magdalena (Studia Edukacyjne, 2023)
Popular culture texts, including films, can be an area of research reflection, e.g. in terms of social phenomena, interpersonal relations, and the interpretation of social roles. The article analyzes the content of selected films by Alfred Hitchcock. The aim of the study was to verify the presentation of the mother-child relationship and the role of the mother. For this purpose, research questions were posed: What image of the mother is presented in Alfred Hitchcock’s films, what are the characteristics of the mother in Alfred Hitchcock’s films, what are the similarities between the image of mother presented by Alfred Hitchcock and socially expected features, what are the differences between the mother’s image presented by Alfred Hitchcock maternal image and socially expected traits? Theses have been developed to answer the above questions and have been verified. A thorough analysis led to conclusions which indicate that the role of the mother had pathological features; kind of pattern of negative traits that the film women took on crystallized. Based on the research, the author defined the role as a “Hitchcock mother type”.